Efektivitas Pengolahan Limbah Minyak Rumah Tangga Terhadap Peningkatan Ekonomi Sebagai Pencegahan Pencemaran Air dan Lingkungan - rahmawati, aulia dwi; ageng saepudin kanda (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Abstrak. The use of cooking oil is generally influenced by the economic level of each household. There are those who only use it once and then it becomes waste for health reasons, but there are also those who use it several times. Using cooking oil repeatedly, can affect the fatty acid content in the oil. On this occasion, researchers chose the Griya Bandung Indah (GBI) Complex. Because it has more than 300 families and is increasing every year, it causes the sources of income for waste oil to increase, plus the number of culinary businesses around the complex is the main source of used cooking oil and there is still a lack of public awareness of the dangers of throwing used cooking oil into the environment or waterways causing the environment to become contaminated. through a questionnaire survey to housewives and culinary entrepreneurs at the GBI Complex. Researchers are targeting the effectiveness of this Household Oil Waste Processing Activity, the impact of disposing of used cooking oil waste into waterways and the surrounding environment causes clogged waterways and unpleasant odors along the water flow, besides that waste used cooking oil can endanger the health of humans and animals. This Household Oil Waste Processing Activity to Improve the Economy and Prevent Water and Environmental Pollution is effective in its implementation for 1 full month in October 2023, after the direction for processing oil waste, at least the community will pay more attention to the waste they produce so that it can be mutually beneficial. from an economic perspective and the surrounding environmental ecosystem.